Plan de Marketing para el Patio de Vehículos Jota Cars, de la Ciudad de Loja - Peralta Jaramillo, José Luis (2017)
The present thesis has as general objective to realize a "MARKETING PLAN FOR THE JOTA CARS PATIO, OF THE CITY OF SHOP", with this work is intended to give a clear vision about the situation in which the company is, so Ensure its stability and expansion in the competitive market. Methods, techniques and procedures for the development of the thesis were used to investigate, develop and verify the veracity of the study, the methods used were: Deductive method applied in research to contrast relevant aspects of the facts and condensed general theories In the theoretical framework and specifically specific in the elaboration of the proposal, the SWOT, matrix EFE, matrix EFI, matrix IE and matrix of high impact. The Inductive Method was used in the study and analysis of the results of the surveys, to later determine general conclusions reached in the research, and it was used in the formulation of strategies and in the proposal to determine objectives, goals Activities that will be carried out in the marketing plan. The research process was supported by key officials from the Jota Cars vehicle yard as well as direct competitors and yard customers. The variables investigated were external and internal, competitive and market, employing for the collection of information interview guides and questionnaires designed for this purpose and applied through interview techniques to key officials, survey of 242 clients and direct observation to Competitors and study company, information that once collected allowed the subsequent analysis and interpretation of the results. The Marketing Plan was structured according to the following logical procedure: Based on the information obtained from the product of the analysis of the external factors, it was possible to determine according to the analysis of the EFE matrix that the weighted result obtained from 2.87 shows that The company is currently taking advantage of the various opportunities offered by its environment, the most representative being the revaluation of used cars due to the quota limit for imports 6 of new vehicles, the improvement of Current socio-economic situation of the population. In relation to the threats, those with the greatest impact are: Safeguards, specific taxes for the purchase and sale of used cars, growth, strengthening and intensity of competition. The competitive analysis carried out shows that the weighted result obtained from 2.97 in relation to the direct competitors identified is lower than these, indicating that the vehicle yard Jota Cars is not positioned in the sector, but demonstrates advantage in relation to The direct competitors in factors such as: Vehicle quality, market experience, competitive prices and safety and legality in the transaction. In the competitive position of the services offered, it can be observed that the study company excels in buying and selling services in factors such as: Price, guarantee in papers and legality of the vehicle, thorough mechanical review, specialized service. In the following point, the Internal Analysis is performed, in which the EFI matrix allows us to know that the company possesses an acceptable percentage of strengths against weaknesses, finding significant strengths at competitive prices, excellent customer service and quality in vehicles; And as more evident weaknesses the company does not have a Marketing Plan, does not provide training to the sales force, and presents a decrease in sales. In the market study carried out with customers, it is found that: the relevant characteristics of 52% of customers indicate the good condition of the vehicles offered, 54% the price, 48% the variety of vehicles and 44% the Customer Support. In the SWOT analysis that summarizes the analysis of the internal and external factors studied, allowing to identify the respective strategies, based on what was built the proposal, which contains three strategic objectives focused on: Achieve 7 growth in sales both at the level Local and regional in the next 3 years. Consolidate the corporate image of the vehicle yard in the local and regional market of used vehicle sales. Expand the participation of Jota Cars in the market within the next 3 years. In order to achieve the objectives set out in this proposal, a total investment of $ 11.395,00 was budgeted. The work finally establishes the conclusions and recommendations, which complement the satisfactory completion of the proposed Marketing Plan.